2007
DOI: 10.1063/1.2743028
|View full text |Cite
|
Sign up to set email alerts
|

Short wavelength electromagnetic propagation in magnetized quantum plasmas

Abstract: The quantum electrodynamical (QED) short wavelength correction on plasma wave propagation for a nonrelativistic quantum plasma is investigated. A general dispersion relation for a thermal multicomponent quantum plasma is derived. It is found that the classical dispersion relation for any wave mode can be modified to include quantum and short wavelength QED effects by simple substitutions of the thermal velocity and the plasma frequency. Furthermore, the dispersion relation has been modified to include QED effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
32
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 66 publications
1
32
0
Order By: Relevance
“…Ref. [59] also shows that the magnitude of the dispersive effects will be different for the two photon modes.…”
Section: B Is It Worthwhile To Further Test Qed?mentioning
confidence: 99%
See 1 more Smart Citation
“…Ref. [59] also shows that the magnitude of the dispersive effects will be different for the two photon modes.…”
Section: B Is It Worthwhile To Further Test Qed?mentioning
confidence: 99%
“…Moreover, it has recently been experimentally shown that quantum dispersive effects are important in inertial confinement plasmas [106]. The list of quantum mechanical effects that can be included in a fluid picture includes the dispersive particle properties accounted for by the Bohm potential [83,84,85,86,87,88,89,90,91,92,93,94], the zero temperature Fermi pressure [83,84,85,86,87], spin properties [95,96,97], certain quantum electrodynamical effects [45,46,59,107], nano-plasmonics devices [108], as well as quantum effects in the classical regime [109,110]. Within such descriptions, [46,59,83,84,85,86,87,95,96,107] a unified picture of quantum and classical collective effects can be obtained.…”
Section: Quantum Plasmasmentioning
confidence: 99%
“…It is the dispersion relation of beam laser propagating in classical magnetized plasma which is as the earlier result [14].…”
mentioning
confidence: 52%
“…For deeply degenerate plasmas, the ion pressure of the threedimensional Fermi gas with thermal temperature T i in energy units is 14,42 …”
Section: ͑8͒mentioning
confidence: 99%